The Intersection of Business Analytics, Project Management, and Product Management in Healthcare (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The convergence of business analytics, project management, and product management is transforming healthcare by enhancing innovation, improving patient outcomes, and increasing operational efficiency. This paper explores how these disciplines interact within healthcare organizations, emphasizing their combined impact on data-driven decision-making, technology development, and patient-centered services. It defines each field in the healthcare context, examines synergies that drive strategic advantages, presents integration methodologies, and analyzes real-world case studies. Challenges such as data silos, regulatory complexity, and organizational resistance are discussed, along with best practices to overcome them. Future trends, including the growing role of predictive and generative AI and the rise of hybrid healthcare product roles, are also considered. By examining how business analytics supports project and product initiatives, and how structured management ensures the success of innovation, this paper provides a strategic roadmap for healthcare organizations seeking to thrive in an increasingly digital, patient-driven environment.